Ceramic fibers do not exhibit larger toxicity in pulmonary epithelial cells than nanoparticles of the same chemical composition. Issue 12 (4th November 2022) - Bacova, Jana; Hromadko, Ludek; Nyvltová, Pavlina; Bruckova, Lenka; Motola, Martin; Bulanek, Roman; Rihova, Martina; Rousar, Tomas; Macak, Jan M.
Abstract : Inorganic fibers and nanoparticles of the same chemical composition induce similar biological effects in pulmonary cells, which means no or negligible toxicity. Abstract : Herein, the first comprehensive toxicity study of Al2 O3, SiO2, ZrO2, TiO2 and WO3 fiber effects in cultured epithelial A549 cells is presented. The fibers were produced by centrifugal spinning from suitable spinning solutions and have an average diameter in the sub-micrometer range. At first, we characterized the fibers for their morphological, compositional and structural properties. Then, we estimated the biological effects of fibers in pulmonary epithelial A549 cells comparing them with the biological effects of Al2 O3, SiO2, ZrO2, TiO2 and WO3 nanoparticles. Multiwalled carbon nanotubes (MWCNTs) were used as a positive control. The cells were treated with 1, 10 and 100 μg mL −1 concentrations of a nanomaterial for 24 and 48 h. The dehydrogenase activity and glutathione levels were determined in cells as markers of cell injury. We found that the tested fibers exhibited no deleterious effects in A549 cells except for Al2 O3 and TiO2 fibers causing significant cell damage of similar extent to Al2 O3 and TiO2 nanoparticles, respectively. Overall, we conclude that the herein tested inorganic fibers do not exhibit larger toxicity risk in human pulmonary A549 cells in comparison to nanoparticles of the same chemical composition.